A study of causes for the failure of cadet and junior medalists of Iran in senior wrestling: perspective of coaches - Khodayari, A.; Babaei Jafari, M.; Asgari, B.; Babaei Jafari, A. (International Journal of Wrestling Science, 2013)
The purpose of this research is to study the causes for the failure of cadet and junior medalists from Iran to continue their success as they move to senior level wrestling from the perspective of coaches. METHODS: The research sample was selected randomly and is included 162 people from grade . and II active coaches of Iran. In this study a researcher-made questionnaire consisting of 35 questions in five subscales including facilities, management, physical fitness, sport injuries and psychological problems. The validity of questionnaire was approved by 7 experts of physical education, and in pilot study of 30 cases from wrestling experts, the reliability of the questionnaire by Cronbach's alpha was measured at 0.80. In order to evaluate and compare the descriptive data used from descriptive and inferential statistical (Friedman test) in SPSS software the significant level was established with p.0.05. RESULTS: Results showed that the greatest impact contributing towards a failure of cadet and junior medalists in senior wrestling was attributed to facilities, management, sport injuries, physical fitness and psychological problems, in that order, respectively. CONCLUSIONS: It is recommended that wrestling federation officials prioritize their attention to these subscales in order to increase the success of the cadet and medalists in senior wrestling. Finally, as was seen in the findings, the main factor of 20 is related to the lack of success of the young teen wrestling medalists at world level in the category of adult age, 18 were related to the facilities and management of the environment. Sports injury, physical fitness and psychological issues remain viewed as having less impact, however, administrators and those involved in the organization of national wrestling should be focused on the facilities and management. It is also possible that if adequate attention is given to these two largest contributors, a lot of obstacles in the remaining three areas, training sports injury, physical fitness and psychological problems, can be dealt with and elevate the role of scientific specialists and trainers.